Separation emulsion via non-ionic surfactant: an optimization - Abdulredha, Murtada Mohammed; Hussain, Siti Aslina; Abdullah, Luqman Chuah (MDPI, 2019)
Achieving emulsion stability in the petroleum industry is a major challenge due to several problems encountered in the oil refining process, such as corrosion in equipment, high-pressure drops in pipelines, and catalyst poisoning in upstream facilities. Thus, several methods are applied for emulsion treatment and chemical treatment using surface-active agents, a fundamental method in the petroleum industry. The present work investigated the performance of a non-ionic surfactant in separating water in a crude oil emulsion via the bottle test technique. Then, a Fractional Factorial Design (2K−1) was used to characterise the effect of significant variables. In particular, a Pareto chart was employed and factors such as demulsifier dosage, toluene concentration, pressure, sitting time, and temperature were investigated. Accordingly, the parameters applied were further analysed using a Central Composite Design (CCD) based on the Response Surface Method (RSM). The experimental results based on analysis of Variance (ANOVA) show that demulsifier dosage, temperature, and sedimentation times were the main variables affecting the dehydration process, with the highest F-values being 564.74, 94.53 and 78.65 respectively. The increase in the surfactant dosage before critical concentration, temperature and sitting time leads to boosting dehydration efficiency. In addition, a mathematical model was established for the variables, with a coefficient of determination value of 0.9688. Finally, numerical optimisation was performed on the variables and the results show that the optimal values are 1000 ppm, 15.5 mL, −400 mmHg, 120 min, and 90 °C, for demulsifier dosage, toluene concentration, pressure, sitting time, and temperature, respectively.